Opioid Overdose Education for Individuals Prescribed Opioids for Pain Management: Randomized Comparison of Two Computer-Based Interventions - Huhn, Andrew S.; Garcia-Romeu, Albert Perez; Dunn, Kelly E. (Frontiers in Psychiatry, 2018)
Background: Opioid overdose (OD) rates in the United States have reached unprecedented levels. Current OD prevention strategies largely consist of distribution of naloxone and in-person trainings, which face obstacles to expedient, widespread dissemination. Web-based interventions have increased opioid OD response knowledge in patients with opioid use disorders; however, these interventions have not been tested in the larger population of individuals that are prescribed opioid analgesics. This study assessed a web-based intervention providing education across three knowledge domains: opioid effects, opioid OD symptoms, and opioid OD response. Methods: Participants (N=197) were adults recruited on Amazon Mechanical Turk from May to June 2017, who were prescribed an opioid medication for pain. Participants were randomly assigned to a Presentation (n=97) intervention communicating relevant facts in each knowledge domain, or a Presentation + Mastery (n=100) intervention including the same facts but requiring that participants respond correctly to >80% of embedded questions in each module before advancing. Participants completed the Brief Opioid Overdose Knowledge (BOOK) measure before and after the interventions, and provided feedback on acceptability. Results: Both versions of the intervention resulted in significant pre- to post-intervention increases in BOOK scores across all knowledge domains (p<.001), with no significant knowledge differences between groups. The Presentation intervention took significantly less time to complete (p<.001), and was completed by significantly more participants than the Presentation + Mastery intervention (p<.001). Most participants rated both interventions as highly acceptable. Conclusion: Results replicate a previous study (Dunn et al., 2017) and suggest the web-based Presentation intervention may be a convenient, cost-effective method for disseminating crucial public health information for preventing opioid OD.